Modelling radioimmunotherapy with anti-CD45 antibody to obtain a more favourable biodistribution - Király, F. J.; Kletting, P.; Reske, S. N.; Glatting, G. (Nuklearmedizin - NuclearMedicine, 2009)
Radioimmunotherapy (RIT) is a method to selectively deliver radiation to malignant haemato logical cells by addressing specific antigens. One approach to improve the bio-distribution is to administer a preload of unlabelled antibodies. The aim of this study was to develop a model, which describes distribution of labelled and unlabelled antibodies based on the tissue blood flow and the competing binding behaviour of the antibodies. Such a model can be used to improve biodistribution in the particular case of RIT using anti-CD45 antibodies. Methods: A compartmental model for the interconnected organs was developed. Reaction constants and organ specific flow, antigen concentrations and distribution volumes were taken from the literature. The organ residence times were calculated for different amounts of given labelled and unlabelled antibodies and the time delay between their administrations. Results: The model is capable to describe the preloading effect. The biodistribution of labelled or unlabelled antibodies depends essentially on the specific blood flow to the organ and its antigen expression. The dose ratio of bone marrow to liver is maximized by applying sufficient unlabelled monoclonal antibody (mAb) to saturate antibody binding in the competing organs and by applying the labelled mAb with a delay of more than one hour. Conclusions: The developed model qualitatively describes how a preload can considerably increase selectivity of RIT due to different blood flows and antigen distribution in relevant organs. In addition, simulations can identify the optimal delay between the application of labelled and unlabelled antibody. For future analyses, i.e., to fit patient data, degradation and excretion should be incorporated into the model.
Keywords: Anti-CD45; biodistribution; preload; compartmental model; numerical simulation